Analysis of Students' Mathematical Problem Solving Ability Based on Self-confidence - Islami, Shinta; Zawawi, Irwani; Khikmiyah, Fatimatul (FKIP Universitas Lampung, 2022)
The purpose of this study was to analyze the ability to solve mathematical problems of students in terms of self-confidence. This type of research is quantitative with a descriptive approach. The data in this study were obtained from tests and questionnaires. The results of the questionnaire were used to classify student’s self-confidence. The test results of the problem solving were then analyzed based on the student’s self-confidence. As a complement to the data on problem solving skills of students, interviews were conducted at each level of self confidence. The results showed that students with high level of self-confidence have excellent problem solving skills with an average value of problem solving skills of 91. Student’s with moderate level of self-confidence have good problem solving skills with an average value of problem solving skills of 74, and student’s with low level of self-confidence have fairly good problem solving skills with an average value of problem solving skills of 51. Keywords: problem solving skill, mathematics, self-confidence. DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1670-1679